Synthesis and Antibacterial Activities of Sulfur-Containing Bissalicylaldehyde Schiff Base and Binuclear Nickel(II) Nanorod Complex - Xiao-Lan Yang; Guo-Qing Zhong; Li Wu (Journal of Chemistry)
Nickel(II) acetate tetrahydrate was treated with the ligand CH2(H2sal-sbdt)2 in methanol heated at reflux to yield a novel binuclear Ni(II) nanorod complex of the formula CH2{Ni(II)(sal-sbdt)(H2O)}2. The ligand of CH2(H2sal-sbdt)2 was derived from 5,5′-methylene-bissalicylaldehyde and S-benzyldithiocarbazate. The complex was characterized by elemental analysis, UV-Vis, FT-IR spectra, thermal analysis (TG-DSC), and scanning electron microscopy (SEM). The nickel(II) was coordinated by imino nitrogen, thiolato sulfur, and phenolic oxygen from the Schiff base ligand, and oxygen from the coordinated water, respectively. The pyrolysis reactions in the thermal decomposition process of the complex, the experimental, and calculated percentage mass loss were also given. The Ni(II) complex belonged to nanocrystalline metal complex, and the average size of the nanorod complex was about 30 nm × 150 nm. The antibacterial activities were screened for the Schiff base ligand and the Ni(II) nanorod complex against four bacteria: Staphylococcus aureus, Escherichia coli, Bacillus subtilis, and Staphylococcus epidermidis. Both the ligand of CH2(H2sal-sbdt)2 and the Ni(II) complex had the most intense antibacterial activities against Escherichia coli.